Hubungan Movement Behavior dengan Health Related Quality of Life pada Siswa/I Smp Tarakanita Citra Raya selama Pandemi Tahun 2021 - Firdani Mutiara; Herwanto Herwanto (Syntax Corporation Indonesia, 2025)
Movement behavior is a combination of motion behavior that includes physical activity, sleep duration, and sedentary behavior. However, during the COVID-19 pandemic, there were several changes in human movement behavior within 24 hours due to the implementation of policies to break the chain of transmission. The impact caused by the implementation of social distancing causes limited human movement that affect the health-related quality of life for each individual, especially on indicators of children's physical, mental and social health. This study aims to see the relationship between movement behavior and health related quality of life in students of SMP Tarakanita Citra Raya during the 2021 pandemic using an analytical method with a cross sectional design. This research was conducted at SMP Tarakanita Citra Raya with 239 respondents consist of 88 male students and 151 female students. Data were collected using the GPAQ questionnaire, sleep duration, and KIDSCREEN-27 which were filled out online in December 2021. The results of this research indicate the characteristics of movement behavior that 74.06% of students do physical activity less than 1680 MET-minutes/week, 65.7% of students have a sleep duration of 6-8 hours per day, 29.29% of students perform sedentary behavior 3-4 hours, 47.28% of students do not meet the recommendation of movement behavior, and 84.94% of students have a good HRQoL. Statistical tests based on the Pearson correlation showed that there was a very weak relationship between physical activity and health related quality of life with a correlation coefficient of 0.177 with p value of 0.006 and the correlation between sleep duration and health related quality of life with a correlation coefficient of 0.190 and a p value of 0.003.